Anti-SARS-CoV-2 antibodies in breast milk during lactation after infection or vaccination: A cohort study. (September 2022) - Olearo, Flaminia; Radmanesh, Laura-Sophie; Felber, Nadine; von Possel, Ronald; Emmerich, Petra; Pekarek, Neele; Pfefferle, Susanne; Nörz, Dominik; Hansen, Gudula; Diemert, Anke; Aepfelbacher, Martin; Hecher, Kurt; et al.
Abstract: Breast milk is a pivotal source to provide passive immunity in newborns over the first few months of life. Very little is known about the antibody transfer levels over the period of breastfeeding. We conducted a prospective study in which we evaluated concentrations of anti-SARS-CoV-2 Spike IgA and RBD IgG/M/A antibodies in maternal serum and breast milk over a duration of up to 6 months after delivery. We compared antibody levels in women with confirmed COVID-19 infection during pregnancy (n = 16) to women with prenatal SARS-CoV-2 vaccination (n = 5). Among the recovered women, n = 7 (44%) had been vaccinated during the lactation period as well. We observed intraindividual moderate positive correlations between antibody levels in maternal serum and breast milk (r = 0.73, p-value<0.0001), whereupon the median levels were generally higher in serum. Anti-RBD IgA/M/G transfer into breast milk was significantly higher in women recovered from COVID-19 and vaccinated during lactation (35.15 AU/ml; IQR 21.96–66.89 AU/ml) compared to the nonvaccinated recovered group (1.26 AU/ml; IQR 0.49–3.81 AU/ml), as well as in the vaccinated only group (4.52 AU/ml; IQR 3.19–6.23 AU/ml). Notably, the antibody level in breast milk post SARS-CoV-2 infection sharply increased following a single dose of vaccine. Breast milk antibodies in all groups showed neutralization capacities against an early pandemic SARS-CoV-2 isolate (HH-1) and moreover, also against the Omicron variant, although with lower antibody titer. Our findings highlight the importance of booster vaccinations especially after SARS-CoV-2 infection in pregnancy in order to optimize protection in mother and newborn. Highlights: Vaccination against SARS-CoV 2 during the lactation period significantly augments the level of antibodies in breast milk. Higher serum antibody levels transpire into breast milk, irrespective of induction by natural infection or vaccination. SARS-CoV-2 antibodies in breast milk had a decreased neutralizing capacity against the omicron variant.